Analisis Energi Baru Terbarukan Untuk Sistem Kelistrikan Desa - Aesha Fathara (Journal of Applied Smart Electrical Network and Systems, 2021)
Electricity is a primary need for society. Energy that will never run out of availability is energy from solar radiation. Indonesia is an agricultural country that can utilize alternative energy by utilizing biomass energy, one of which is rice husk and straw waste. Based on data from the BMKG Paloh Station, Sambas Regency has a fairly large intensity of sunlight because it is located just below the equator. The intensity of light in the dry season can reach 6 hours in a period of 8 hours of sunlight, namely from 8.00 - 16.00. The resulting energy conversion is 38.01 mj/m2/day. Meanwhile, for the biomass potential from the BPS data of Sambas Regency in Tebas District, there are 6,730 ha of rice fields, which can produce 403 tons of rice husk and straw waste in one day for 1 year and can produce 5 million Mj/day . The results of the conversion analysis of the optimization of renewable energy for power plants that have an annual peak power of 45kW and daily energy consumption of 330kWh/day obtained the most optimal potential for rice husk and straw waste, which requires an initial capital of $ 67,120 with a total net present minimum cost. Electricity from the system cost is also minimum at US$ 0.005/kWh. And in technical economic analysis, modeling this system requires a payback period of about 11 years without grid bills and 5 years with grid bills. Meanwhile, conversion using PV requires larger capital and longer payback.